Dynamics Response of Indonesian Islamic Law to the Protection of Intellectual Property Rights - Asmuni, Asmuni; Yusdani, Yusdani; Arfaizar, Januariansyah (Ulumuna, 2023)
Every work of innovation is a valuable intellectual property that should be protected by the state, according to Law No. 24 of 2014. However, Intellectual Property Rights are not adhered to by the public as there is much piracy. This is evident in the proliferation of websites providing pirated music, photocopies of books, and uploading songs that are sung again without permission from the creator. This necessitates a study related to the protection of Intellectual Property Rights (IPR) from the perspective of Islamic law. Building on the theory of maqasid sharia, the study shows that Islamic law views copyright as protected property because it is haq al-ibtikar containing the creator's exclusive, economic, and moral rights. From a fiqh perspective, the solution should be based on moral and economic demands. Therefore, it is necessary to strictly enforce the law against violations of Intellectual Property Rights because it is based on the appreciation and protection of creative rights, which signify professionalism.